Price responsive demand in Britain's electricity market - Emmanuele Bobbio; Simon Brandkamp; Stephanie Chan; Peter C. Cramton; David Malec; Lucy Yu (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2022)
Electricity markets balance supply and demand with price. Historically, this price response has come almost entirely from supply. However, when much of supply is intermittent or inflexible, price responsive demand becomes essential for reliability and resiliency. We measure how responsive consumers are to price in Britain from July 2020 to July 2021 with half-hourly individual-household data. Our sample includes customers with a dynamic rate that tracks wholesale cost, as well as flat-rate customers used to control for weather and other factors. A one percent increase in price reduces demand by 0.26 percent. This elasticity is larger for consumers owning low-carbon technologies. This price response is sufficient to maintain system balance in extreme events even when most consumers are unresponsive. Regulators can encourage price responsive demand through retail choice and subsidize enabling technologies. Regulators can protect consumers with mandated hedging in dynamic plans. Low-income households benefit most from such policies.
Keywords: 330